Imperativeness of Higher Education in Developing Human Capital-A Contemporary Analysis of Malaysia - Panda, Sitansu (2018)
The changing nature; style and habit of people have accentuated business organizations to explore new strategies for their success. The role of institution for higher education especially technical universities needs a special mention. The role, responsibility, contribution, commitment, citizenship behaviour and over & above dedication of technical universities in developing human capital for excelling Malaysian economy are being highlighted in this study. Excellence is an outcome of continuous perseverance which should be the thrust and practice in developing human capital. The goals of different Malaysian National Plans like Vision 2020, Vision 2050 and One Nation based on the needs, demands and global changes along with the tunes of Fourth Industrial Revolution can be fulfilled for which the technical universities have to play an important role. The road ahead is bright for Malaysia. However, more collaborative efforts among institutions and industries from the field of industrial engineering, business management, innovative enterprise, industrial psychology and healthcare management are important in order· to make the country socially great, economically bright and be a role model for others.